Molecular regulation of GABAergic neuron differentiation and diversity in the developing midbrain. (8th February 2013) - Lahti, L.; Achim, K.; Partanen, J.
Abstract The midbrain GABAergic neurones control several aspects of behaviour, play important roles in psychiatric disease and are targets of medical treatments as well as drugs of abuse. However, their molecular diversity and regulation of development are only beginning to be understood. In this review, we briefly introduce distinct subpopulations of the midbrain GABAergic neurones and discuss knowledge on their development, including the developmental origins of midbrain GABAergic neurones as well as transcriptional regulatory mechanisms guiding their differentiation and identity. Important GABAergic neuron subpopulations are found within the dopaminergic (DA) nuclei in the ventral midbrain. GABAergic substantia nigra pars reticulata is the main output pathway of the basal ganglia system regulating voluntary movements. Recent studies have also highlighted importance of the GABAergic neurones associated with the ventral tegmental area for the control of DA neuron activity and motivated behaviours. Interestingly, the development of the GABAergic neurones associated with the DA nuclei is very different from the rest of the midbrain. Knowledge on developmental regulation can lead to insights into the molecular, structural and functional diversity of the midbrain GABAergic neurones and their subpopulations, cell groups of great physiological and medical interest.